Preservasi dan Konservasi Delapan Naskah Keislaman - Ahmad Hanafi (Moderasi : Journal of Islamic Studies, 2022)
Manuscripts is the result of handwriting which contains various things such as thoughts, community culture, history of one's life journey and customs in the past. Religious texts are related to the spread of religion in Jember, such as there are Islamic boarding school texts for the spread of Islam and there are Bible texts for the spread of Christianity in Jember.. The research was conducted using a philological research method with a codicological approach. There are several steps in this research method. First, tracing the manuscripts obtained from the people who inherited the manuscripts. Second, an inventory of manuscripts is carried out by means of field studies, namely visiting directly the location where the manuscripts are stored by the community who is the owner or inheritor of the manuscripts. Third, preservation by caring for and maintaining the manuscript to prevent the loss of the information contained in the manuscript due to damage to the manuscript due to certain factors. The results of this study explain aspects of codicology, manuscript descriptions and efforts to save the findings of eight ancient manuscripts in Jember Regency. .